Readiness of Electronic Medical Record Implementation at Budi Asih Trenggalek Hospital using the Fishbone Diagram Method - Chery Putria Santoso; Ani Rosita (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2025)
The electronic medical record (EMR) is an important step in supporting the digitization of health services, with the aim of improving the effectiveness, efficiency and accuracy of the management of patient medical data in hospitals. This study aims to determine the readiness of the implementation of RME in BUDIASIH Hospital Trenggalek by using the Fishbone Diagram method as an analytical tool in identifying the factors that influence.This study uses a descriptive method with a qualitative approach to explore the implementation process in depth. The Data was obtained through in-depth interviews and direct observation to 20 informants who actively use the RME system in the implementation of daily tasks.The results showed that the readiness of RME implementation in Budi Asih Hospital was influenced by five main factors, namely man (Human Resources), matherial (tools), machine (data), method (methods), and money (budget). Health workers and administrative staff have been able to operate RME well, accompanied by regular training and workshops to improve understanding related to System updates. Equipment and support systems are available and functioning properly, along with scheduled maintenance to keep the system running stably. Data management has been done accurately and timely, supported by periodic audits to maintain the quality and validity of the data. The hospital also has a clear Standard Operating Procedure (SOP) I n the implementation of RME and has allocated a budget to support the sustainability of this system. Overall, Budi Asih Trenggalek Hospital has shown good readiness in the implementation of RME and is ready to develop this system to support the improvement of the quality of health services in the future.This study recommends increased maintenance of software and hardware as well as regular training of human resources to support the sustainability of the RME system.